OPTIMIZATION OF THE SURGICAL METHOD FOR REMOVING DENTAL IMPLANTS THAT HAVE LOST FUNCTIONAL VALUE (Ustozlar uchun, 2026)
As a method for restoring the integrity of dentition, dental implantation has proven its high efficiency. Despite a significant rate of implant survival and success after 5–10 years of functioning, the number of complications has increased in recent years. According to global estimates, approximately 2 million implants are placed annually, while 200,000–250,000 are removed each year.Purpose of the study: To optimize the surgical method for removing dental implants that have lost their functional value.